Civic Crowdfunding: Systematic Literature Review and Future Research Agenda - Milosavljević, Miloš; Milanović, Nemanja; Spasenić, Željko; Benković, Slađana (E-business technologies conference proceedings, 2021)
In the last few years, civic crowdfunding has been receiving a growing attention among scholars and practitioners in various fields, ranging from technology to public administration. Civic crowdfunding is a sub-class of crowdfunding in which citizens collaborate with government to (co-)finance public goods or services. Although it is an interesting and promising area for both research and application, only a paucity of attention has been given to broad literature review. The main aim of this paper is to provide a systematic literature review in this worldwide early stage of the development of civic crowdfunding. To address this aim Scopus database was browsed and the total of 71 papers were analyzed. The results indicate a number of opportunities and challenges which were discussed in the Serbian context.